A BOUNDARY ELEMENT FORMULATION FOR MASONRY WALLS: ELASTIC-LINEAR ANALYSIS - Oliveira Neto, L. [UNESP]; Masia, M. J.; Rigitano, A. C. [UNESP]; Taguti, Y. [UNESP]; Ingham, J.; Dhanasekar, M.; Masia, M. (9th Australasian Masonry Conference, 2011)
This work presents an application of a Boundary Element Method (BEM) formulation for anisotropic body analysis. The formulation is elaborated for elastic-linear analysis, using isotropic fundamental solution, in which it is necessary to take account of anisotropy in this type of structure. The anisotropy is considered by expressing a residual elastic tensor as the difference of the anisotropic and isotropic elastic tensors. Also considered are the internal variables and cell discretization of the domain. The paper presents the completed formulation, the method for obtaining the elastic tensor of the anisotropic medium properties and the algebraic procedure. Some examples are shown to validate the formulation.